Exploration of Psychosocial Hazards of Job Context Among Academics at Malaysian Private Research-Focused Universities -Case Study - HanizaAbdul Khalid; Ahmad Shahrul Nizam Isha; Marlia Puteh; Al-Baraa Abdulrahman Al-Mekhlafi (International Journal of Academic Research in Progressive Education and Development, 2024)
Indexed by ERA